Diagnostic study of the Food Planning and Monitoring Unit (FPMU) in Bangladesh: Current structure, output, and analytical capacity (human and logistical) - Dorosh, Paul A.; Ali, Shawkat; Bin Khaled, Muhammad Nahian; Mustafa, Shoumi (International Food Policy Research Institute, 2021)
For almost fifty years, the Food Planning and Monitoring Unit (FPMU) of the Ministry of Food has played a role in analysis and planning related to the Public Foodgrain Distribution System (PFDS) and food in Bangladesh. Supported by a series of major donor-funded technical sup-port projects, this small unit has had major positive impacts on food reforms, as well as decisions on timing of PFDS imports, domestic procurement and distribution. And in the last dec-ade, the FPMU has played a lead role in formulation and monitoring of Country Investment Plans for Agriculture, Food Security and Nutrition. Thus, the FPMU provides support not only to the Ministry of Food, but nine other ministries, as well. This expanded mandate and the increased complexity of food and nutrition in Bangladesh suggest the need for an in-depth examination of the FPMU’s structure and performance. This diag-nostic study, based on a review of documents, interviews of FPMU staff and other government offi-cials, stakeholder consultations and synthesis of findings, assesses the organizational structure, management, technical performance (data management and direct support to food implemen-tation) and capacity strengthening needs to provide insights on how to further enhance the FPMU’s effectiveness.